Increased serum concentrations of macrophage inhibitory cytokine-1 in patients with obesity and type 2 diabetes mellitus: the influence of very low calorie diet - Dostálová, Ivana; Roubícek, Tomás; Bártlová, Markéta; Mráz, Milos; Lacinová, Zdena; Haluzíková, Denisa; Kaválková, Petra; Matoulek, Martin; Kasalicky, Mojmír; Haluzík, Martin (European journal of endocrinology, 2009)
OBJECTIVE: Macrophage inhibitory cytokine-1 (MIC-1) is a novel regulator of energy homeostasis. We explored whether alterations in MIC-1 levels contribute to metabolic disturbances in patients with obesity and/or obesity and type 2 diabetes mellitus (T2DM). DESIGN: We measured serum MIC-1 levels and its mRNA expression in subcutaneous and visceral adipose tissue of 17 obese nondiabetic women, 14 obese women with T2DM and 23 healthy lean women. We also explored the relationship of MIC-1 with anthropometric and biochemical parameters and studied the influence of 2-week very low calorie diet (VLCD) on serum MIC-1 levels. METHODS: Serum MIC-1 levels were measured by ELISA and its mRNA expression was determined by RT-PCR. RESULTS: Both obese and T2DM group had significantly elevated serum MIC-1 levels relative to controls. T2DM group had significantly higher serum MIC-1 levels relative to obese group. Serum MIC-1 positively correlated with body weight, body fat, and serum levels of triglycerides, glucose, HbAlc, and C-reactive protein and it was inversely related to serum high-density lipoprotein cholesterol. Fat mRNA MIC-1 expression did not significantly differ between lean and obese women but it was significantly higher in subcutaneous than in visceral fat in both groups. VLCD significantly increased serum MIC-1 levels in obese but not T2DM group. CONCLUSION: Elevated MIC-1 levels in patients with obesity are further increased by the presence of T2DM. We suggest that in contrast to patients with cancer cachexia, increased MIC-1 levels in obese patients and diabetic patients do not induce weight loss.
Keywords: dospělí; Caloric Restriction; Female; Adult; ženské pohlaví; růstový diferenciační faktor 15; Diabetes Mellitus, Type 2; Obesity; hubenost; lidé; Thinness; diabetes mellitus 2. typu; messenger RNA; RNA, Messenger; dieta; Humans; Middle Aged; Weight Loss; tělesná hmotnost; obezita; Diet; Growth Differentiation Factor 15; hmotnostní úbytek; Body Weight; lidé středního věku; tuková tkáň; kalorická restrikce; Adipose Tissue